Implementasi Kebijakan Keuangan Daerah Dalam Menangani Pandemi Covid-19 Di Badan Pengelolaan Keuangan Dan Aset Daerah Provinsi Sumatera Utara - Adha Sauvana; Bahrum Jamil; Nina Angelia (Universitas Medan Area, 2022)
The handling of Covid-19 is directed at the government to take quick action to make policies that are in accordance with the needs of accelerating the spread of Covid-19, especially in the financial sector. This researcher is in the form of a descriptive qualitative approach, namely describing the data obtained from the field and explaining it in words. This study aims to analyze the implementation of regional financial policies in handling Covid-19 in North Sumatra Province. Based on the data that has been collected, it can be seen from several indicators from George C. Edward III's theory, namely communication, resources, disposition and bureaucratic structure that have been used to see how the implementation of regional financial policies in North Sumatra Province, in the implementation of these policies there are several obstacles in terms of communication and poor resources caused by the Covid-19 virus. So that the implementation of regional financial policies in dealing with Covid-19 in North Sumatra Province cannot be realized properly.